2022
DOI: 10.1002/pam.22460
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Exchange and Tax Compliance: Evidence From a Field Experiment

Abstract: Behavioral interventions appealing to taxpayers' reciprocity often leave tax compliance unaffected. We provide evidence that a "fiscal exchange nudge" increased tax compliance in a setting where one might not expect it: crisis-ridden Argentina. In a randomized controlled trial with over 20,000 taxpayers, a tax bill visually celebrating realized public works benefiting children increased payment rates of tax delinquents by about 20 percent, or almost 40 percent when the bills were delivered in person. Without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Tax administration is one of the main fields of nudge experimentation (for Brazil, see Schächtele et al, 2022). Some of the BIT's (2011b) trials with behavioural insights applied to tax collection showed that using social norm messages can lead individuals to pay their tax debts more quickly, and that highlighting key messages and norms can lead to higher response rates.…”
Section: Dirección Y Organizaciónmentioning
confidence: 99%
“…Tax administration is one of the main fields of nudge experimentation (for Brazil, see Schächtele et al, 2022). Some of the BIT's (2011b) trials with behavioural insights applied to tax collection showed that using social norm messages can lead individuals to pay their tax debts more quickly, and that highlighting key messages and norms can lead to higher response rates.…”
Section: Dirección Y Organizaciónmentioning
confidence: 99%